Optimasi Hasil Produksi Konveksi dan Bordir Komputer pada CV. Jonifer Embroidery Menggunakan Metode Branch and Bound - suci wulandari; muhammad subhan (Journal of Mathematics UNP, 2019)
Abstract — Every company generally has various problems in achieving business objectives. CV. Jonifer Embroidery has the limited machine resources and employee to achieve optimal profits. The purpose of this study is to form the model and the results of production on CV.Jonifer Embroidery using Branch and Bound method. Branch and Bound method is a method for solving linear optimization problems to obtain integer variables. On CV. Jonifer Embroidery optimal production obtained are 152 pieces of long-sleeved shirt, 192 pieces of short shirt, 213 shirts, 165 pieces of collared shirts, 92 jackets and 148 pieces of salempang with optimal profits of Rp.22.295.400. Keywords — Branch and Bound, Linear Programming, Optimization, Production.